1995
DOI: 10.1111/j.1365-2915.1995.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Gambian children to Anopheles gambiae malaria vectors in an irrigated rice production area

Abstract: Variation in exposure of children to malaria vectors of the Anopheles gambiae complex was recorded in a Gambian village situated near an irrigated area of rice cultivation. Observations were made in 1987 and 1988 during two dry seasons, when pumped water was used to grow rice, and two rainy seasons, when rice was produced using a combination of irrigated and rainfed paddies. Routine collections of mosquitoes were made from under bednets. Most of these specimens were assumed to have fed on the occupants of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 26 publications
2
63
1
Order By: Relevance
“…By contrast, the design of houses may reduce the degree of exposure to blood-seeking mosquitoes, as simple construction may act as a physical barrier to prevent mosquitoes from entering . Houses with open eaves, mud rather than stone walls, and thatched roofing, as well as those occupied by a greater number of people and those without ceilings or cooking fires, were all associated with increased vector densities (Adiamah et al 1993;Lindblade et al 2000;Lindsay et al 1995;Palsson et al 2004;Zhou et al 2007). The apparent increase in the number of mosquito bites also had an effect on morbidity levels, since such housing conditions were associated with increased morbidity (Adiamah et al 1993;Ghebreyesus et al 2000;Koram et al 1995;Ong'echa et al 2006;Somi et al 2007;Ye et al 2006).…”
Section: Ecological Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the design of houses may reduce the degree of exposure to blood-seeking mosquitoes, as simple construction may act as a physical barrier to prevent mosquitoes from entering . Houses with open eaves, mud rather than stone walls, and thatched roofing, as well as those occupied by a greater number of people and those without ceilings or cooking fires, were all associated with increased vector densities (Adiamah et al 1993;Lindblade et al 2000;Lindsay et al 1995;Palsson et al 2004;Zhou et al 2007). The apparent increase in the number of mosquito bites also had an effect on morbidity levels, since such housing conditions were associated with increased morbidity (Adiamah et al 1993;Ghebreyesus et al 2000;Koram et al 1995;Ong'echa et al 2006;Somi et al 2007;Ye et al 2006).…”
Section: Ecological Interactionsmentioning
confidence: 99%
“…distance to breeding sites Malaria has been associated with the presence and proximity of marsh areashence the name "mal aria" or "bad air"-since the earliest descriptions of the disease and its symptoms. Studies on the proximity of water bodies, either natural or manmade, showed that indoor vector densities were higher close to breeding sites (Lindsay et al 1995;Minakawa et al 2002a;Minakawa et al 2004) and that malaria risk was, consequently, increased in these areas (Bøgh et al 2007;Clarke et al 2002;Ghebreyesus et al 1999;Kleinschmidt et al 2001;Lautze et al 2007;Oesterholt et al 2006;Staedke et al 2003;Trape et al 1992). Interestingly, Clarke et al (2002) noted that, although risk in terms of exposure was decreased farther away from water bodies, clinical illness was more common, probably as a result of reduced immunity due to lower exposure to infective bites.…”
Section: Entomological Parameters and Thementioning
confidence: 99%
“…Other studies have shown that malaria increases as the distance to standing water decreases (Coosemans et al, 1984;Lindsay et al, 1995;Ghebreyesus et al, 1998Ghebreyesus et al, , 1999Ghebreyesus et al, , 2000, which also acts to increase human-vector contact. Efforts to control malaria must include a comprehensive assessment of factors that affect the propensity of an area to harbour anopheline mosquitoes, and factors associated with malaria and the use of malaria and mosquito control tools.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, accurate age grading methods are essential for estimation of mosquito survival, which is the most important biological determinant of transmission intensity 24,25 and may vary over scales as fine as a kilometer or less, 26,27 presumably underpinning much of the fine-scale variation in malaria transmission exposure that exists in human populations. [28][29][30] Until recently, few methods have been available for the agegrading of African anophelines. Most age-grading analyses have been based on somewhat crude categorization of females into groups of nulliparous (typically less than four days of age) or parous 31 as assessed by ovarian dissection, which is a skilled, labor-intensive, and time-consuming method.…”
Section: Introductionmentioning
confidence: 99%